The 2019 ESPEN Arvid Wretlind lecture perioperative nutritional and metabolic care: patient-tailored or organ-specific approach? - Gianotti, Luca; Sandini, Marta (Clinical nutrition, 2020)
Background & aim - The perioperative severe changes in the nutritional and metabolic homeostasis are, by some means, proportional to the extent of tissue injury and magnitude of operative trauma. An adequate qualitative and quantitative replacement of nutritional substrates are of utmost importance to facilitate proper tissue healing and recovery and maintenance of organ function after surgery. - Methods - The present manuscript has been planned to put the most recent research of the Milano-Bicocca University surgical working group in the context of a more personalized nutritional therapy and metabolic care for surgical patients. Particular prominence has been given to major pancreatic resections because these surgeries are among the most complex and challenging operations for the degree of parenchyma resection and tissue dissection, the consequent overall injury, and the fairly high rate of major complications resulting in a catabolic response. - Results - Anthropometric parameters and particularly sarcopenia, visceral obesity - and their relative proportion -, are strongly associated with poor outcome after pancreatic surgery. Adequate perioperative nutritional therapy is of utmost importance in affecting morbidity. Long-term nutritional and metabolic sequelae, caused by exocrine pancreatic insufficiency, need to be promptly recognized and treated with an adequate enzyme supplementation. - Conclusions - There is strong evidence sustaining the necessity of proper perioperative metabolic and nutritional care into the management of patients undergoing major pancreatic surgery.